Perempuan Kajang dalam Sebagai Penjaga Nilai Etika dan Moral di Tengah Arus Wisata Digital - Renaldi, Renaldi; Kartini, Kartini; Sasha, Andi; Awaru, Andi Octamaya Tendri; Khairunniza, Liza Dwi Eftiza (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Online tourism and social media have transformed the way people view and experience local culture, including the Kajang Dalam indigenous community, which maintains strict ethical, moral, and modesty rules. The purpose of this study is to demonstrate how Kajang Dalam women maintain and disseminate traditional values amidst digital trends that drive increased tourist visits. The study will also examine how they communicate through visual representations that often do not align with the cultural context. This research utilizes qualitative methods by conducting semi-structured interviews with indigenous women, tourism practitioners, and purposively selected traditional leaders. To analyze the data thematically, source triangulation and cross-checking with informants were used to ensure credibility. The results show that Kajang Dalam women maintain moral values, regulate social etiquette, and are active cultural interpreters, asserting customary boundaries within digital tourism practices. They reprimand moral violations, educate tourists, and limit the use of technology in certain traditional areas, serving as a bridge between tradition and change. The results suggest that women play a strategic role in maintaining cultural resilience and strengthening community identity amidst the digitalization of tourism.